Neuroanatomical correlates of impulsive action in excoriation (skin-picking) disorder - Blum, Austin W. (J Neuropsychiatry Clin Neurosci, 2018)
Excoriation (skin-picking) disorder (SPD) has similarities to obsessive-compulsive disorder (OCD) and is included within the obsessive-compulsive and related disorders (OCRD) category in DSM-5. Separate neuroimaging and neurocognitive studies in SPD implicate difficulty with motor response inhibition and top-down cognitive control in the disorder. No study, however, has examined the neural correlates of SPD in participants with varying degrees of impulsive motor behavior. This study correlated cortical thickness and volumes of selected subcortical structures with stop-signal task performance in participants with SPD (N = 15) and healthy controls (N = 8). All participants were free from current psychiatric comorbidity, including OCD. In individuals with SPD, longer stop-signal reaction times were correlated with cortical thinning in the right insula and right inferior parietal lobe, and increased cortical thickness in the left lateral occipital lobe (p < 0.001 uncorrected), though these findings did not withstand correction for multiple comparisons. There were no significant correlations between cortical thickness in these three structures and stop-signal reaction times in the control group. This study suggests that structural abnormalities in the insular cortex and parietal and occipital regions may play a role in the pathophysiology of SPD. Further neuroimaging research is needed to understand the neurobiology of SPD and its relationship with other OCRDs.